2010
DOI: 10.1590/s1808-86942010000600019
|View full text |Cite
|
Sign up to set email alerts
|

Traqueobroncopatia osteocondroplástica: relato de 2 casos e revisão bibliográfica

Abstract: Ost eochondroplastic tracheobronchopathy (OT) is a rare benign disorder of the lower part of the trachea and the upper part of the main bronchus characterized by numerous submucosal calcified nodules, sessile, cartilaginous and/or osseous with laryngotracheobronchial lumen projection. There are less than 400 cases reported in the word literature.Aim: to report and discuss 02 cases of OT with a bibliography review. Materials and Methods:we report on 02 cases with bibliography revision from MEDLINE, LILACS and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Aschoff-Freiburg reported changes to the tracheal elastic tissue, and used the term osteoplastic tracheopathy to describe the condition, and similarly, in 1964, Secrest et al labeled it osteoplastic tracheobronchopathy. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aschoff-Freiburg reported changes to the tracheal elastic tissue, and used the term osteoplastic tracheopathy to describe the condition, and similarly, in 1964, Secrest et al labeled it osteoplastic tracheobronchopathy. 3 …”
Section: Discussionmentioning
confidence: 99%
“…4 According to Secrest, it is estimated that only 5% of the cases are diagnosed during the person's life. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from overseas showed that there was no significant difference in the prevalence of TO between males and females [7]. It was also reported that the prevalence of TO between males and females was about 3 : 1 [8]. In China, there was no significant difference regarding the prevalence of TO between males and females in most studies [2].…”
Section: Discussionmentioning
confidence: 99%
“…e first case of TO was recorded abroad in 1855. It was reported that there was no significant difference in the prevalence rate between men and women [7], while others reported that the prevalence rate was about 3 : 1 for men and women [8]. e pathogenesis of TO is unknown, which may be related to congenital tracheobronchial dysplasia, long-term physical, chemical, or mechanical stimulation, chronic inflammation, and metabolic disorders [6].…”
Section: Introductionmentioning
confidence: 99%